Iron Granular Percolative Composites toward Radio-Frequency Negative Permittivity. (7th September 2018) - Jiang, Yuliang; Xie, Peitao; Wang, Zhongyang; Fan, Guohua; Qu, Yunpeng; Sun, Kai; Man, Han; Zhang, Zidong; Liu, Yao; Fan, Runhua
Abstract : The immense potential of metamaterials with negative electromagnetic parameters has propelled recent research and development. Here, the two-phase composites with Fe or insulated PVP-coated Fe powders dispersed in epoxy resin were prepared by blending and hot-molding procedure. Microstructures, ac conductivity, permittivity, and permeability of the resulted composites were investigated at 10 MHz-1 GHz region. Three-dimensional conductive networks were constructed when the Fe content exceeds the percolation threshold, where the conduction mechanism changed from hopping conduction to metal-like conduction. Negative permittivity behavior was attributed to low-frequency plasma oscillation of delocalize electrons explained by Drude model. Besides, the diamagnetism of current loops induced by external magnetic field lead to the negative magnetic susceptibility. After Fe particles were coated by insulated PVP, permittivity was positive and there is no longer obvious diamagnetic phenomenon, indicating that insulating layer changed the conductive path in composites. This work opens up a promising strategy to tune negative permittivity and permeability which will facilitate applications in electromagnetic cloaking, absorbing, attenuation and so on.